Leigh's Disease: The Acute Clinical Course of a Two-Year-Old Child with Subacute Necrotizing Encephalomyelopathy - Bettina Zinka; Andreas Buettner; Matthias Graw (Case Reports in Medicine)
We report the untypical clinical course of a previously healthy two-year-old girl, who died suddenly and unexpectedly after an episode of vomiting. At forensic autopsy no other pathological findings could be diagnosed than multiple reddish, sunken areas in brain stem, mesencephalon, and pons. Histologically they presented as areas of spongiosis of the neuropil with prominent endothelial hyperplasia and vascular proliferation whereas nerve cells were well preserved. On the basis of the characteristic neuropathological findings in combination with the age of the child, we had to take into consideration that the child might have died from subacute necrotizing encephalomyelopathy (Leigh's Disease) despite the untypical, fulminant clinical course.